The Role of Platelet-Rich Plasma in Reducing Pain, Pruritus, and Improving Wound Healing of Skin Graft Donor Site - Muhammad Tahir, Shahzad Shaikh, Aamna Sanober, Yasir Arfat Memon, Mujtaba Pervez Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Wound healing is an intricate and interactive process. As a result, no single operator can efficiently and successfully help to resolve all attributes of healing process. The goal of the study that PRP was to systematically perceive the stimulatory effect at multiple stages during wound healing and trying to identify tissue repair mechanisms, lower pain, itching skin and healing time. Study design: This was a cross sectional study and carried out at plastic surgery department of Ghulam Muhammad Mahar Medical College Hospital, Sukkur for the duration of six months from June 2022 to December 2022. Methods: 120 participants which include male n=80 and female included n=40 who under the observation of split skin grafting due to reason of injuries, burning, accidents and traumas. These participants divide into two category of treatment for example, paraffin gauze dressing and platelet rich plasma (PRP). The age of participants between >20 and <50 years. To examine the preparation method of PRP, raw area dressing and clinical outcome for the assessment of pain, pruritus before and after comparison of gauze dressing and PRP. The data was analyzed by SPSS 21 version. Results: The total participants are 120 in this study and the age group between 20 and 50 with an average age was 35 years. The affected area was left leg was 25% and right leg 75%. The raw area in 54.1% participants was burn and 46% participants were by road accident. The dressing was changed alternate weeks. The treatment with PRP showed significant changing in the effective participants as compared to paraffin gauze dressing (p<0.05). Conclusion: PRP serves as a delivery system for growth factors, making this blood product extremely useful for use in a variety of indications in plastic and reconstructive surgery. Intradermal injection of platelet rich plasma is a secure and efficient option for minimizing pain, adverse reactions, and ability to heal multiple injuries in patients with burns and radiation injuries. Keyword: Platelet rich plasma, wound healing, itching skin, growth factors